BIMBINGAN CALISTUNG KEPADA ORANG TUA USIA LANJUT YANG MENYANDANG TUNA AKSARA DI DESA SUMBERKARE PROBOLINGGO - Musthofa, Ahmad; Muhaimin Akhmadi, Abdul; Andika, M.; Qodir, Abd.; Prasetiya, Benny (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to guide older people who are illiterate in improving their learning abilities and understanding, as well as helping them adapt. It is hoped that this will be useful for them in overcoming daily problems and challenges that may arise in their work environment caused by the lack of economic factors in Sumberkare Village, Wonomerto District, Probolinggo Regency. Poverty is a major factor that makes a person illiterate. It will be difficult for someone who experiences poverty to attend school because they have to struggle to fulfill their daily needs. The method used is a qualitative method with a descriptive approach. where the researcher acts as the main instrument. Data collection techniques involve observation, interviews, and documentation. In addition, data analysis was carried out with the aim of finding the authenticity of the data and evaluating the information collected.